Tumor thrombus: A rare cause of acute stroke (Indian Journal of Case Reports, 2024)
Stroke is common in our everyday practice as doctors and radiologists. The stroke pathways have steadily improved over the last number of years with the advent of dedicated stroke units; synchronized streamlined care with endovascular stroke therapies, leading to improved outcomes. We present the case of a 57-year-old woman complaining of sudden onset right-sided facial droop and right-sided weakness. The case represents an unusual cause for an atypical stroke with multiple learning outcomes.